The Role of Osteocytes in Inflammatory Bone Loss - Metzger, Corinne E.; Narayanan, S. Anand (Frontiers in Endocrinology, 2019)
Osteoimmunology investigations to-date have demonstrated the significant interactions between bone surface cells, osteoclasts and osteoblasts, and immune cells. However, there is a paucity of knowledge on osteocytes, cells embedded in the bone matrix, and their role in inflammation and inflammatory bone loss. Osteocytes communicate through various mechanisms; directly via dendritic processes and through secretion of proteins that can influence the formation and activity of osteoblasts and osteoclasts. Some osteocyte proteins (e.g., interleukin-6 and RANKL) also have roles within the immune system. In the context of mechanical loading/unloading, the regulatory role of osteocytes is well understood. More recent data on osteocytes in various inflammatory models suggest they may also aid in orchestrating inflammation-induced changes in bone turnover. In inflammatory conditions, osteocytes express multiple pro-inflammatory cytokines which are associated with increases in bone resorption and declines in bone formation. Cytokines are known to also influence cell population growth, maturation, and responsiveness via various signaling modalities, but how they influence osteocytes has not been greatly explored. Furthermore, osteocytes may play regulatory roles in orchestrating bone’s response to immunological changes in inflammatory conditions. This review will address what is known about osteocyte biology in physiological conditions and in response to varying immunological conditions, as well as highlight key areas of interest for future investigations.